2019
DOI: 10.3233/hsm-190548
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of intrapreneurial personality in relation between leader humility and innovative behavior

Abstract: This quantitative study empirically analyzes the relation between leader humility and innovative behavior by assessing the moderating role of intrapreneurial personality. Cross-sectional data were collected from 498 respondents in Karachi, Pakistan. The study has two purposes. First, on the basis of signaling theory, it investigates the relation between leader behavior (humility) and innovative behavior (at the individual level). Second, on the basis of personality and individual differences it considers follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In the same vein, another study used a five-dimensional model to investigate the telecommunications sector in China and concluded that justice is positively associated with innovative behaviors (Akram et al, 2020). Further, Abbas and Wu (2019b) used a sample from Pakistan-a South Asian country-and found that leader humility is significantly and positively related to innovative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, another study used a five-dimensional model to investigate the telecommunications sector in China and concluded that justice is positively associated with innovative behaviors (Akram et al, 2020). Further, Abbas and Wu (2019b) used a sample from Pakistan-a South Asian country-and found that leader humility is significantly and positively related to innovative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have discovered the link between humble leadership and various employee outcomes (Abbas and Wu, 2019;Kausar, 2020;Ali et al, 2021;Waseem et al, 2023), our study is one of the few empirical works explicitly examining the association between humble leadership and creative performance (CP). By empirically establishing this relationship, our research extends the understanding of how humble leadership, with its focus on collaboration, openness, and acknowledging contributions, can positively influence employees' creative performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the field of humble leadership (HL) have investigated its positive impact on project success in the Pakistani context (Ali et al, 2020(Ali et al, , 2021Waseem et al, 2023). Furthermore, studies in the same context have explored the role of HL in influencing career success, employee creativity, follower emotions, ethical behavior, and work engagement (Abbas and Wu, 2019;Kausar, 2020;Naseer et al, 2020;Abbas et al, 2021). These existing literatures provide a solid foundation for conducting our study within this specified context.…”
Section: Research Context Sample and Data Collectionmentioning
confidence: 99%
“…HL has been previously associated with different employee outcomes [67,68]. HL can significantly foster the WREN level of employees [69].…”
Section: Theory and Hypothesesmentioning
confidence: 98%